Impact of lockdown and school closure on children during the COVID-19 pandemic - Luis Rajmil (Elsevier, 2024)
This brief communication reports the conclusions of a narrative review study on the impact of Lockdown and School Closure on Children During the COVID-19 Pandemic. The objective was to analyze social inequalities in child health, before, during and after the pandemic, in a range of child health outcomes related to school closures and other lockdown measures.